Doorways and Diegesis: Spatial and Narrative Boundaries in Apuleius' Metamorphoses. - Beck, Bill (Classical Philology, 2022)
This article argues that the difficulties that characters in Apuleius' Metamorphoses experience at doorways symbolize, and often coincide with, the difficulties that readers experience in their attempts to negotiate the novel's diegetic boundaries. Part 1 argues that the extensive overlap between the novel's characters—in particular, Lucius, Aristomenes, Socrates, and Thelyphron, the sources of the novel's first four extended narratives—complicates readers' ability to negotiate narrative boundaries. Part 2 argues that readers find spatial analogues for their diegetic difficulties in scenes in which characters encounter difficulties at locked doors.